Hospital Digital Marketing: Challenges and Adaptations in Facing Competition in Indonesia - Sulaiman, Benedict; Darmayanti, Ni Putu Diah Utami; Faridah, Iva Nur (CV. Publikasi Indonesia, 2024)
The global healthcare industry is undergoing a significant transformation driven by technological advancements and evolving patient expectations. This study aims to analyze the challenges and adaptations of digital marketing strategies in Indonesian hospitals, emphasizing the transformative impact of digital platforms like YouTube and Instagram on patient engagement and healthcare service delivery. Using a qualitative case study approach, data were collected through interviews with hospital stakeholders, document analysis, and observations of digital practices. The findings highlight that effective digital marketing strategies improve hospital visibility and patient relationships, while challenges such as fragmented health data, inadequate infrastructure, and insufficient regulations hinder progress. The study concludes that addressing these challenges through targeted investments and comprehensive legal frameworks can significantly enhance the global competitiveness of Indonesian hospitals. These insights offer practical implications for adopting ethical and sustainable digital marketing practices in the healthcare sector.